Sterling-dollar diplomacy in current perspective : the origins and the prospects of our international economic order - Gardner, Richard N. (New York : Columbia University Press, 1980)
This is a book about the making of international economic policy and the shaping of institutions to implement that policy. It places special emphasis on the interaction between official policy and public opinion; particularly on the difficult problem of explaining complex economic policies to a democratic electorate. Thus it is a hybrid work on the borderline of history, international relations, political science, and even international law.
Reprint of the new, expanded ed. published in 1969 by McGraw-Hill, New York under title: Sterling-dollar diplomacy.
Includes index.
Includes bibliographical references: p. 393-412.
ne 06/05/2018
Loans
Keywords: Currency question; International economic relations; United States; Great Britain